What's a Drink with Friends?: A Qualitative Systematic Synthesis of Social Drinking as Leisure. (23rd November 2020) - Burns, Robyn; Gallant, Karen A.
Abstract: To enrich our understanding of how leisure scholars are engaged in the topic of social drinking, this qualitative systematic synthesis consolidates and describes leisure literature related to social drinking. Following Saini and Shlonsky's (2012 ) methods for systematic syntheses of qualitative literature, this review included articles from 11 leisure journals, published between 2006 and 2016, resulting in a total of 249 abstracts reviewed. Upon applying inclusion criteria to focus the review on descriptions of social drinking, 17 articles were included in the synthesis and analysis. Notably, descriptions of social drinking in the leisure literature are less common than those which emphasize the broad health implications. Descriptions of social drinking are most present when presented as an adjunct to another leisure pursuit, as in the context of sporting events and tourism.